SIMULATING DISPERSIVE MIXING IN LARGE PEATLANDS - Reeve A.S.; Siegel D.I.; Glaser P.H. (My University, 2001)
Numerical simulations indicate that mechanical dispersive mixing can be the dominant mass transport mechanism in large peatlands. Dispersive mixing driven by lateral flow can drive solute fluxes from the mineral soil upward to the peat surface and thereby explain observed patterns of bog and fen in large peatlands. Longitudinal and transverse dispersivities of only 0.5 and 0.05 m, respectively, were sufficient to supply solutes to the peat surface in the absence of upward ground-water flow. Incorporation of hydrodynamic dispersion in peatland systems explains apparent contradictions in solute migration in peatlands, allowing the simultaneous downward flux of labile carbon (i.e. root exudates) produced at the peat surface and upward migration of inorganic solutes from the underlying mineral soil. Previous models of peatland hydrogeochemistry that rely on advection alone as the dominant process for solute transport may therefore be inadequate to explain fully the hydrology, geochemistry, and evolution of large peatlands.